Factors affecting the retention of healthcare assistants in English mental health services: a qualitative interview study - Michaela Senek; Jaqui Long; Sally Ohlsen; Rachael Finn; Scott Weich; Tony Ryan; Emily Wood (BMC Health Services Research)
Abstract Background In the UK, healthcare assistants (HCAs) work alongside registered nurses and other clinicians to provide frontline clinical care. HCAs provide a considerable amount of essential direct patient care which, dependent on the setting, can include monitoring of temperature, pulse, respirations and ECGs, support with daily activities, emotional support and facilitating communication with other health professionals. In 2019, the leaver rate of HCAs and support workers in the UK was 13.4%. In many Trusts this was higher than the leaving rate for nurses. The aim of this study was to explore HCAs’ experiences and their perceptions of the reasons for poor retention rates. Methods We recruited HCAs from three English mental health Trusts. Recruitment information was circulated using a variety of approaches. 31 participants took part in semi-structured interviews. We explored the factors they considered to affect HCAs’ decision to leave their role, and any differences they perceived with registered staff. Interviews were coded and analysed using the framework generated in a previous phase of the study which focused on retention of registered mental health professionals. Findings Three key factors impacted HCAs job satisfaction, wellbeing, and motivation to remain in post: (1) high workloads and unclear role boundaries creating stress and concerns for patient care; (2) good relationships with line managers and colleagues providing essential support to cope with both work and personal challenges; (3) feeling undervalued by the wider organisation, with a lack of investment including pay, facilities, and opportunities for development. These factors combined to create a situation of high stress and low job satisfaction, with many HCAs expressing an intention or desire to leave, particularly when the pay is similar to much less demanding jobs in other sectors. Conclusions HCAs are a diverse group but many reported job dissatisfaction and feeling undervalued by the organisations they work for, with some struggling to cope with the cost-of-living crisis. Improved role boundaries, career pathways, and appreciation of the role such as reward and recognition schemes, could help retain this key staff group who provide a large proportion of essential patient care.